2001
DOI: 10.1001/jama.285.17.2199
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Events Recorded on Home Monitors

Abstract: In this study, conventional events are quite common, even in healthy term infants. Extreme events were common only in preterm infants, and their timing suggests that they are not likely to be immediate precursors to SIDS. The high frequency of obstructed breathing in study participants would likely preclude detection of many events by conventional techniques. These data should be important for designing future monitors and determining if an infant is likely to be at risk for a cardiorespiratory event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
171
0
10

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 328 publications
(189 citation statements)
references
References 22 publications
8
171
0
10
Order By: Relevance
“…A previous longitudinal study also identified "extreme" events that occurred with comparable frequency in otherwise normal term infants and that were not statistically increased in term infants with a history of ALTE. 34 Preterm infants have been shown to have more serious events, although an ALTE does not further increase that risk compared with asymptomatic preterm infants without ALTE. 34 Claudius and Keens 31 performed an observational prospective study in 59 infants presenting with ALTE who had been born at >30 weeks' gestation and had no significant medical illness.…”
Section: A Clinicians Need Not Admit Infants Presenting With a Lowementioning
confidence: 94%
“…A previous longitudinal study also identified "extreme" events that occurred with comparable frequency in otherwise normal term infants and that were not statistically increased in term infants with a history of ALTE. 34 Preterm infants have been shown to have more serious events, although an ALTE does not further increase that risk compared with asymptomatic preterm infants without ALTE. 34 Claudius and Keens 31 performed an observational prospective study in 59 infants presenting with ALTE who had been born at >30 weeks' gestation and had no significant medical illness.…”
Section: A Clinicians Need Not Admit Infants Presenting With a Lowementioning
confidence: 94%
“…Previous work 5 suggests that apnea and bradycardia are more common in premature infants than in healthy term infants or infants with idiopathic apnea and that this risk remains elevated until 43 weeks' PMA. Much of the earlier work on the epidemiology of apnea and bradycardia within premature infants centers on the effect of gestational age on the timing of the last apnea or bradycardia event.…”
Section: Figurementioning
confidence: 99%
“…Short, self-limited events or obstructive events without apnea may have been missed. 5 As a result, when a health care provider decided to discharge a patient may marginally affect these results for those infants discharged relatively soon after their last apnea or bradycardia event. This study also used information from a limited number of NICUs because of the difficulty in collecting detailed data on respiratory maturity from a large number of premature infants with complete postdischarge data.…”
Section: Figurementioning
confidence: 99%
“…In the Collaborative Home Infant Monitoring Evaluation (CHIME) study, the symptomatic group of preterm infants at 42 to 45 weeks postconceptional age and thereafter had events similar to term controls. 100 Physiological basis for the resolution of apnea is believed to be myelination of the brainstem. Evidence supporting this notion was provided by an elegant study by Henderson-Smart et al 101 Utilizing auditory evoked responses, these investigators studied a group of babies with and without apnea and showed that brainstem conduction time was shorter in infants without apnea when compared to preterm infants with apnea.…”
Section: Other Therapiesmentioning
confidence: 99%